Manfish : a story of Jacques Cousteau - Berne, Jennifer; Puybaret, Eric (San Francisco : Chronicle Books, 2008)
An illustrated biography of Jacques Cousteau, discussing how his youthful fascinations with filming and underwater exploration translated into his life's work, and telling of his later devotion to saving the ocean environment.
Booklist starred
School Library Journal
Wilson's Children
Book Links-starred, October 2008
Booklist starred, June 2008
Bulletin (Center for Children's books), July 2008
Keywords: Cousteau, Jacques, -- 1910-1997 -- Juvenile literature; Cousteau, Jacques, -- 1910-1997.; Cousteau, Jacques Yves; Cousteau, Jacques, -- 1910-1997.; Oceanographers -- France -- Biography -- Juvenile literature; Oceanographers -- Biography; Oceanographers -- Biography